Key Gingival Dimensions and Shapes of Maxillary Lateral Incisors in a Middle East Population – A Preliminary Report - Shreya Shetty; Khamarunissah Sheikh; Hashim Hamzah A Alaidaroos; Khlood Hamed Alghamdi; Omnia Ashraf Mohammed Zaghloul (The Bioscan, 2025)
Background: Numerous studies have demonstrated that the shape, size, angulation, and position of the maxillary lateral incisor significantly influence smile esthetics. The relationship of the lateral incisor to adjacent teeth—particularly the central incisor and canine—often described by the "Golden Proportion," also affects the perception of smile harmony. The purpose of this study was to evaluate whether a correlation exists between maxillary lateral incisor crown shapes and various periodontal parameters, including gingival and interdental characteristics. Materials and Methods: Clinical measurements were collected from 60 systemically healthy male and female individuals aged 21–35 years. Parameters recorded for each participant included crown width (CW), crown length (CL), height of the interproximal papilla (Ph), gingival angle (GA), mesiodistal width (MDW), and contact surface length (CS) of the maxillary lateral incisors. Based on the CW/CL ratio, participants were categorized into three crown shape groups: tapered, square, or ovoid. These groups were compared for statistically significant differences in clinical parameters using appropriate statistical methods (ANOVA and post-hoc tests). Results: Statistically significant differences (P < 0.05) were observed among the three tooth shape groups with respect to gingival angle, mesiodistal width-to-crown length (MDW/CL) ratio, and contact surface length (CS). Ovoid and square-shaped incisors showed particularly strong associations with CS and CS/CL ratios, while MDW/CL differed significantly across all groups. Conclusion: Tooth shape is significantly associated with variations in gingival angle, contact surface length, and the MDW/CL ratio. These findings support the use of tooth morphology as a reliable clinical indicator in esthetic treatment planning for restorative and prosthodontic procedures involving the maxillary lateral incisors.